PENGARUH USER GENERATED CONTENT (UGC) DAN BRAND EQUITY PADA GREEN PURCHASE (STUDI PADA KONSUMEN THE BODY SHOP DI BRAZIL DAN INDONESIA) - Imella Yusdike Onny; Andriani Kusumawati (Fakultas Ilmu Administrasi Universitas Brawijaya, 2019)
User Generated Content (UGC) can be said as a complete definition of product ulasan. Together with Brand Equity, both have influenced consumers on their decisions toward a Green Purchase. This research is conducted on The Body Shops’s consumers in Brazil and Indonesia. The aim of this research is to (1) examine the influence of User Generated Content (UGC) on Green Purchase, (2) examine the influence of Brand Equity on Green Purchase, (3) examine the influence of User Generated Content (UGC) and Brand Equity on Green Purchase simultaneously, (4) examine the differences in perception on the influence of User Generated Content (UGC) and Brand Equity on Green Purchase between Brazilian (resides in Brazil) and Indonesian (resides in Indonesia) consumers. The type of this research is explanatory research with a quantitative approach. The sampling technique used is purposive sampling and the method of collecting data through an online questionnaire via Google form to 120 respondents. The data analysis used is descriptive analysis, classic assumption test, multiple linear regression analysis, and independent sample t test. Kеywоrds: User Generated Content (UGC), Brand Equity, Green Purchase АBSTRАK User Generated Content (UGC) dapat dikatakan sebuah definisi lengkap dari ulasan produk. Bersama Brand Equity, keduanya mempengaruhi keputusan konsumen terhadap Green Purchase. Penelitian dilakukan pada konsumen The Body Shop di Brazil dan Indonesia. Tujuan penelitian ini adalah untuk (1) menjelaskan pengaruh User Generated Content (UGC) terhadap Green Purchase, (2) menjelaskan pengaruh Brand Equity terhadap Green Purchase, (3) menjelaskan pengaruh User Generated Content (UGC) dan Brand Equity terhadap Green Purchase, (4) menjelaskan perbedaan persepsi pada pengaruh User Generated Content (UGC) dan Brand Equity terhadap Green Purchase antara konsumen Brazil (Warga negara Brazil dan bertempat tinggal di Brazil) dan konsumen Indonesia (Warga negara Indonesia dan bertempat tinggal di Indonesia). Jenis penelitian adalah eksplanatori dengan pendekatan kuantitatif. Teknik pengambilan sampel adalah purposive sampling serta metode pengumpulan data melalui online kuisioner menggunakan Google form pada 120 responden. Data analisis yang digunakan adalah analisis deskriptif, uji asumsi klasik, analisis jalur berganda, dan independent sample t test. Kata Kunci: User Generated Content (UGC), Brand Equity, Green Purchase